Perceived social support and sleep quality in patients with arteriosclerotic obliterans: The mediating roles of psychological flexibility - Ying Lu; Hongyan Gan; Yanyan Yuan; Chunyan Zheng; Liping Bai; Zhuanfang Zou; Yujin Yang (Wiley, 2023)
Abstract Aim The aim of the study was to investigate the effect of perceived social support (PSS) on sleep quality in arteriosclerotic obliterans patients in China and examined whether psychological flexibility (PF) has a mediating effect between PSS and sleep quality. Design A cross‐sectional survey. Methods A cross‐sectional study was conducted between September 2020 and December 2021 on 172 patients with atherosclerotic obliterans recruited from a hospital in China. Results PSS was negatively associated with sleep quality and PF, whereas PF was positively associated with sleep quality. This relationship between PSS and sleep quality was mediated by PF. Patient or public contribution Vascular surgery specialist nurses assisted the members of the research group in distributing the questionnaires after the patients gave oral informed consent, and the patients cooperated to complete the questionnaires. We thank both parties for their contributions to this survey.